Simplify 12e − 5f − 7e +3f .

1 answer

To simplify the expression 12e − 5f − 7e +3f, we can combine like terms.

The terms 12e and -7e can be combined because they have the same variable and exponent. When we combine them, we get 12e - 7e = 5e.

Similarly, the terms -5f and 3f can be combined because they have the same variable and exponent. When we combine them, we get -5f + 3f = -2f.

Therefore, the simplified expression is 5e - 2f.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions